Adaptation of Staphylococcus aureus to the Human Skin Environment Identified Using an ex vivo Tissue Model - Burian, Marc; Plange, Johanna; Schmitt, Laurenz; Kaschke, Anke; Marquardt, Yvonne; Huth, Laura; Baron, Jens M.; Hornef, Mathias W.; Wolz, Christiane; Yazdi, Amir S. (Frontiers in Microbiology, 2021)
The healthy human epidermis provides physical protection and is impenetrable for pathogenic microbes. Nevertheless, commensal and pathogen bacteria such as Staphylococcus aureus are able to colonize the skin surface, which may subsequently lead to infection. To identify and characterize regulatory elements facilitating adaptation of S. aureus to the human skin environment we used ex vivo tissue explants and quantified S. aureus gene transcription during co-culture. This analysis provided evidence for a significant downregulation of the global virulence regulator agr upon initial contact with skin, regardless of the growth phase of S. aureus prior to co-culture. In contrast, the alternative sigma factor B (sigB) and the antimicrobial peptide-sensing system (graRS) were expressed during early colonization. Consistently, tissue adherence was mediated by the sigB target genes clumping factor A (clfA) and fibrinogen and fibronectin binding protein A (fnbA). At later timepoints of the adhesion process, wall teichoic acid (WTA) synthesis was induced. Besides the expression of adhesive molecules immune evasion by transcription of the staphylococcal complement inhibitor (scn) and staphylokinase (sak) contributed to the colonization of S. aureus. Similar to nasal colonization, enzymes involved in cell wall metabolism (sceD and atlA) were heavily transcribed. Finally, we detected a strong expression of proteases from all three catalytic classes during the entire colonization process. Taken together, we here present a novel ex vivo skin colonization model that allows the detailed characterization of the bacterial adaptation to the skin environment.